PERAN KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA GURU SMA NEGERI DI KOTA SUKABUMI - Edy Mulyadi Soepardi (Universitas Pakuan, 2013)
This research can be classified in a correlational study that consists of two independent variables, namely the Principal Leadership and Teacher Work Motivation and one dependent variable, namely Teacher Job Satisfaction. This study was conducted at five state Senior High Schools at South Tangerang City in 2012 with total sample of 129 people taken with proportional random sampling technique. The method used is survey and data analysis techniques using correlation and regression statistical. The hypothesis testing performed on the significant level of 0.05 and 0,01. The results of the study showed that: First, there is positive and highly significant correlation between principals leadership with teachers job satisfaction with correlation coefficient, ry1 = 0.5683 and regression equation ? = 78.042 +0.382X1. Second, there is positive and highly significant correlation between work motivation with teacher job satisfaction, with correlation coefficient ry2 = 0.5974, and regression equation ?=50.497+0.573X2. Third, there is positive and highly significant correlation between principal leadership and work motivation all together with teacher job satisfaction with correlation coeficient ry1,2 = 0.7125, and regression equation, ?=31.738+0.278X1 + 0.438X? Based on the result above it can be concluded that teachers job satisfaction can be improved through principal's leadership and work motivation.Keywords : teachers job satisfaction, principal's leadership and work motivation.